MILLENNIAL GENERATION CONCEPTION ABOUT ISLAMOPHOBIC, DE- RADICALIZATION AND COMMUNICATION PROCESS BASED ON MULTICULTURAL EDUCATION: A PHENOMENOGRAPHY STUDY - PRIYOWIDODO, GATUT (Universitas Muhammadiyah Yogyakarta, 2019)
Islamphobic is a mind-set of fear about everything about Islam. The countenance of Islam as 'rahmatan lil alamin' (bringing peace to all people), is affected by acts of violence and terror that are often displayed by a group of radical Muslims. The purpose of this research is to find out how the description of the understanding of Islamophobic among Christians, especially the millennial generation in Indonesia. It is related to the countenance of violence that is often done by some Muslims who in fact do not reflect the overall attitude of Islamic Teachings in Indonesia. Through phenomenography study the data was collected from all interviewees, related to certain conceptions or conceptions expressed by each individual. The characteristics of the informants are those who are a generation of Christian millennial who have easy access to information. The findings of this study propose that Islamphobic is conceptualized as a form of fear. It is because of the countenance of Islam which is portrayed as full of violence, radical acts, discriminatory, hatred and raises fear among non-Islamic Followers. The attempt to de-radicalize was conceived successfully by the government because it was considered the right way to reduce feelings of fear and anxiety among non-Muslims. In addition, through the process of communication and multicultural education, it is expected to bridging the meeting of different views and is very relevant for diversity in Indonesia.Â Â